CD9, a novel potential biomarker of sarcopenia - Lin Yin; Na Li; Peirong Bai; Shasha Wu; Xuena Wang; Bin Lu (Scientific Reports)
Abstract Sarcopenia is defined as a progressive decrease in skeletal muscle mass and strength due to ageing, and is associated with adverse outcomes such as falls, fractures, and physical disability, leading to increased healthcare expenditures and mortality risks. Although sarcopenia has recently become a major challenge, there are currently no effective interventions or drugs marketed for sarcopenia. Therefore, new biomarkers for early diagnosis and targeted drugs for the treatment of sarcopenia are urgently needed. In the present research, transcriptomics and proteomics analyses were combined and experiments at the transcriptional and protein levels were conducted to identify key genes and molecular mechanisms underlying sarcopenia in senescence-accelerated mouse prone 8 (SAM-P8) mice, followed by molecular docking to predict targeted drugs. The combined omics analysis identified 8 key genes, while the experiments verified that only CD9 significantly decreased in sarcopenia. The gene set enrichment analysis (GSEA) results suggested that CD9 involved in ATP biosynthesis, mitochondrial biogenesis, and oxidative phosphorylation. Besides, dapoxetine, levomilnacipran, and milnacipran were predicted to target CD9 through molecular docking. Our study reported for the first time that CD9 is a novel potential biomarker of sarcopenia, and targeting CD9 may be a new idea for the development of therapeutic drugs for sarcopenia.